2010
DOI: 10.4103/0022-3859.68647
|View full text |Cite
|
Sign up to set email alerts
|

Maternal indicators and obstetric outcome in the north Indian population

Abstract: A prepregnancy weight of more than 40 kg, BMI of more than 19.8 and hemoglobin of at least 7 g% or more favor good obstetric outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 11 publications
2
39
0
3
Order By: Relevance
“…In our study, infants born to 36% mothers with GWG <9 kgs were at increased risk for fetal growth deficits, which is similar to a study from north India. 6 45.5% women were anemic (Hb < 10.9 gm%) similar to other studies 3,7,8 and were more likely to have a low birth weight baby. However, 27 mothers with normal BMI (>18.5) had a low …”
Section: Discussionsupporting
confidence: 88%
“…In our study, infants born to 36% mothers with GWG <9 kgs were at increased risk for fetal growth deficits, which is similar to a study from north India. 6 45.5% women were anemic (Hb < 10.9 gm%) similar to other studies 3,7,8 and were more likely to have a low birth weight baby. However, 27 mothers with normal BMI (>18.5) had a low …”
Section: Discussionsupporting
confidence: 88%
“…Studies done by Kumar et al, Malhotra et al and K Jagdish et al [10][11][12] had shown such an association only when mothers are severely anaemic. However study done by Xiong X et al 6 shows no significant difference in gestational age and birth weight between anaemic and control group.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] On the other hand prevalence of late pregnancy (in fourth decade or above) is relatively lowers (6.5%) in India. 12 Trends seen in Indian subcontinent reveal that rates of child bearing is maximum between 20 to 30 years of age and prevalence of pregnancy beyond the age of 30 years is relatively lower. 13,14 The findings of present study also endorsed maximum proportion of women in 20-30 years age group and pregnancy beyond 30 years to be minimum.…”
Section: Discussionmentioning
confidence: 99%